Lost in translation? The challenges of measuring informal care among children and young people. (30th October 2017) - Kelly, Grace; Devine, Paula; McKnight, Martina
Abstract : This article uses data from the 2015 Young Life and Times and Kids' Life and Times surveys to discuss the methodological challenges of identifying young carers in surveys. The article considers how children's interpretation of 'caring' might not correspond with the definition of 'young carer' that adults wish to capture. This article discusses how prior consultation with young carers to improve understanding did not have the outcome anticipated. It advises that consultation should be carried out with young carers and their non-caregiving peers together, allowing space for 'co-reflexive practice'.